2021
DOI: 10.3389/fimmu.2021.665160
|View full text |Cite
|
Sign up to set email alerts
|

Shared Genetic Liability Between Major Depressive Disorder and Atopic Diseases

Abstract: ObjectivesDeciphering the genetic relationships between major depressive disorder (MDD) and atopic diseases (asthma, hay fever, and eczema) may facilitate understanding of their biological mechanisms as well as the development of novel treatment regimens. Here we tested the genetic correlation between MDD and atopic diseases by linkage disequilibrium score regression.MethodsA polygenic overlap analysis was performed to estimate shared genetic variations between the two diseases. Causal relationships between MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…First, although we have excluded potential pleiotropic SNPs and MR-Egger regression indicated little horizontal pleiotropy, the influence of pleiotropy bias remains a concern in this study. Specifically, psychiatric traits such as major depressive disorder and neuroticism may be confounding factors in the causal associations between asthma and CVDs ( Cao et al, 2021 ; Wu et al, 2021 ; Zhang et al, 2021 , 2022 ). Besides, the divergent results of sensitivity analyses may indicate a bias of genetic pleiotropy towards asthma-AF and asthma-HF associations that we observed.…”
Section: Discussionmentioning
confidence: 99%
“…First, although we have excluded potential pleiotropic SNPs and MR-Egger regression indicated little horizontal pleiotropy, the influence of pleiotropy bias remains a concern in this study. Specifically, psychiatric traits such as major depressive disorder and neuroticism may be confounding factors in the causal associations between asthma and CVDs ( Cao et al, 2021 ; Wu et al, 2021 ; Zhang et al, 2021 , 2022 ). Besides, the divergent results of sensitivity analyses may indicate a bias of genetic pleiotropy towards asthma-AF and asthma-HF associations that we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies on other populations are therefore warranted. Second, some psychiatric traits (such as major depressive disorder (MDD) and neuroticism) shared genetic liability with AD and CVDs ( 53 55 ). Specifically, there is a bidirectional causal association between MDD and AD ( 53 ), and MDD can lead to a higher risk of CVDs ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, some psychiatric traits (such as major depressive disorder (MDD) and neuroticism) shared genetic liability with AD and CVDs ( 53 55 ). Specifically, there is a bidirectional causal association between MDD and AD ( 53 ), and MDD can lead to a higher risk of CVDs ( 54 ). Therefore, the influence of potential pleiotropy remains a concern in this MR study, despite the lack of evidence from MR-Egger regression and MR-PRESSO methods.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have identified some shared genetic traits between those with asthma and MDD [20,21]. In a cross-trait meta-analysis, Zhu et al, (2019) [20] identified 10 genomic loci shared between asthma and MDD and mendelian randomization identified a significant causal effect of MDD on asthma.…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-trait meta-analysis, Zhu et al, (2019) [20] identified 10 genomic loci shared between asthma and MDD and mendelian randomization identified a significant causal effect of MDD on asthma. The cross-trait meta-analysis performed by Cao et al, (2021) [21] identified 18 loci jointly associated between MDD and atopic diseases (asthma, eczema, and hay fever). Through Mendelian randomization analysis the investigators found that MDD confers a stronger causal effect on those atopic diseases than they confer on MDD.…”
Section: Introductionmentioning
confidence: 99%